Cytotoxic Activity of the Indonesian Fern Angiopteris angustifolia C. Presl and Liverwort Mastigophora diclados (Birs. ex Web) Nees Against Breast Cancer Cell Lines (MCF-7) - Ismiarni Komala; Stevani Sitorus; Fitri Ratna Dewi; Nurmeilis Nurmeilis; Laifa Annisa Hendarmin (Jurnal Kimia Valensi, 2022)
Breast cancer is the most frequent cancer among women worldwide, and it is also the main cause of death from cancer. Fern Angiopteris angustifolia C. Presl and Liverwort Mastigophora diclados (Birs.ex Web) Nees are the plants that grow in Indonesia that are limited explored for their phytochemical and biological activity. This study aims to evaluate the cytotoxic effect of ethanolic extracts leaves of A. angustifolia and M. diclados against breast cancer cell lines (MCF-7). The MTT assay was used to determine cytotoxic activity, which revealed that the ethanol extract of A. Angustifolia and M. diclados exhibited cytotoxic activity with an IC50 value of 121.8 ± 13.3 and 29.2 ±1.4 µg /mL, respectively.